ARTROPLASTIA DE LA ARTICULACIÓN TEMPORO-MANDIBULAR Y EMPLEO DEL ACTIVADOR INTRAORAL. - Merino Martijena, Adolfo (1998)
Sixty Clinic Quirurgical Cases were Diagnostic with Anquilosis by the Pre Articular (Arthoplastic) Technique Using the Intra-Oral Activator design by the Author of this research the results were satisfactory in the one hundred per-cent of the treated cases.This Technique has the advantage of being very confortable don't cause pain is of casy manipulation and health in the rehabilitation process allowing the masticate recuperation and the mandible movements.